Efektivitas Sasaran Bantuan Langsung Tunai di Desa Pakuluruan, Kecamatan Koroncong, Kabupaten Pandeglang - Anilah Anilah; Rijal Rijal; Ari Supriadi (Pusat Riset dan Inovasi Nasional, 2024)
This research focuses on how well the effectiveness of Direct Cash Transfer (BLT) Program from Village Fund (DD) in Pakuluran Village, Koroncong Sub-district, Pandeglang Regency. The purpose of this research is to describe and analyze how the implementation of the BLT Program originating from DD for Beneficiary Families (KPM) in Pakuluran Village, Koroncong District, This research method uses descriptive qualitative methods. The data obtained in this study through data analysis techniques in the field, which include data collection activities, data reduction, data presentation, and conclusion drawing. The results showed that : (Particularly in the context of handling the impact of Covid-19, the economic impact, the Pakuluran Village Government provides BLT sourced from DD and then distributed to the community through a timing mechanism. (2) The effectiveness of the BLT plan in terms of the timeliness of the BLT distribution was on time and followed the existing mechanism. At the same time, looking from the side to make an accurate selection, the village government followed the procedure. The targeting accuracy aspect showed that the BLT distribution from DD was right on target. Based on the results of the research and discussion presented by the researcher regarding the targeted Effectiveness of Village Fund Cash Assistance (BLT) for the community of Pakuluran Village, Koroncong Sub-district, Pandeglang Regency, it can be concluded that the distribution of BLT DD for the community of Pakuluran Village, Koroncong Sub-district, Pandeglang Regency, is considered effective.